Validity of Biological Father Marrying Daughter Resulting from Adultery: Perspective of Nahdlatul Ulama and Muhammadiyah - Moh. Subhan (Al-Mawaddah: Jurnal Studi Islam dan Hukum Keluarga (Ahwal Al-Syakhsiyyah), 2025)
This study explores the validity of marriage between a biological father and his illegitimate daughter according to the two largest Islamic organizations in Indonesia: Nahdlatul Ulama (NU) and Muhammadiyah. NU’s marriage opinion uses Shafi’i jurisprudence that a biological father has no blood relationship with a child from an extramarital affair, so marriage is permissible. However, they withdrew this practice in the bahtsul masail decision because it is contrary to the public interest, and the principle of harm related to children. On the other hand, Muhammadiyah firmly rejects the validity of marriage on the grounds that there is a biological kinship relationship. This gives rise to a mahram relationship. Muhammadiyah also base their opinion on the maqasid sharia and legal recognition in the Constitutional Court Decision No. 46/PUU-VIII/2010. This study uses a normative juridical method with a conceptual and descriptive-analytical approach. The findings of this study indicate a lack of specific and fair regulations aimed at fulfilling the rights of illegitimate children within the framework of family law in Indonesian Islamic law.